More simple solution of not so simple problems – how does it happen? - Kašuba, Romualdas (Lietuvos matematikos rinkinys, 2023)
Several non-standard problems are regarded and the possibilities of simple approaching to their solution are regarded and discussed.
Keywords: subsets; divisibility; representations